INFLUENCE OF TEACHERS’ INSTRUCTIONAL AND CLASSROOM MANAGEMENT PRACTICES ON STUDENTS’ ACADEMIC PERFORMANCE IN PUBLIC SECONDARY SCHOOLS IN SAMETA SUB-COUNTY, KISII COUNTY, KENYA - , Julius Ndigwa Onyango; Simon Nyakwara, (IJRDO - Journal of Social Science and Humanities Research, 2020)
There has been a concerted effort by the government to improve students’ academic performance in secondary schools. Thus, the purpose of the study was to determine the influence of teachers’ instructional and classroom management practices on students’ academic performance in public secondary schools in Sameta Sub-County, Kenya. The study adopted a descriptive survey research design, with a target population of 350 persons, this comprised of 21 Head teachers and 329 teachers. The sample size of 176 persons was determined using the Krejcie & Morgan table (1970). The researcher collected data using questionnaires and interview guides. The instruments were validated by the supervisors. Reliability of the instruments was determined through a pilot study where Spearman’s rank correlation coefficient (r) was analyzed for the two scores and found to be 0.78, thus, the instruments were reliable. Quantitative data was analyzed using descriptive and inferential statistics, and presented in tables, while, qualitative data was analyzed using the common themes, qualitative data extracted, organized and then discussed under the main objective areas of the study. The study established that there is a statistical significant association between teachers’ instructional and classroom management practices and students’ academic performance. It was therefore recommended that head teachers, administration, policy makers and other stakeholders should consider incorporating teachers’ efficacy on various practices such as teacher’s instructional, classroom management, motivation and interpersonal relationships, as this will enhance secondary school students’ performance.